OPTIMALISASI PENGGUNAAN AKUN BELAJAR.ID DALAM PEMBELAJARAN DIGITAL DI SEKOLAH - Fitria, Rezki Nurma; Khamidi, Amrozi; Hariyati, Nunuk; Haq, Mohammad Syahidul; Andari, Shelly; Wulandari, Ayu; Nuphanudin, Nuphanudin; Ghozali, Ghozali (Jurnal Manajemen Pendidikan, 2025)
Launch expected belajar.id account can help with activity learning, but the reality is that there are still lots of schools that do not​ activate belajar.id account and not use the facility as well as maybe. Optimization uses belajar.id account is very important in the context of digital education in Indonesia. Digitalization in continuous learning​ development in a way massive and dynamic can become an opportunity, at times a challenge, to empower the Indonesian generation as an asset nation in the era of revolution 4.0. Although accounts give access to various educational platforms and resources learn a lot school Still face challenges in maximizing their use. Research: This aim for describe the implementation use belajar.id account and efforts for optimizing digital learning in schools. Research methods use a qualitative approach with techniques for data collection through interviews, observations, and study documentation. Analysis techniques are done simultaneously through data condensation, data presentation, and data retrieval. Research results show the implementation of the belajar.id account has implemented in schools, services that are often used are Google Classroom, Canva, and Email for Education.